Pengolahan Daun Kelor (Maringa Oleifera) dan Jahe (Zingiber Officinale) menjadi Teh Herbal (Kadar Air) dan (Uji Organoleptik) Alternatif sebagai Minuman Fungsional Bernilai Gizi - Agung Rizki; Sisilia Florina Yanti; Candra Sigalingging (Kampus Akademik Publiser, 2026)
Moringa leaves are highly nutritious functional food ingredients but have a beany flavor and bitter taste, while ginger has a distinctive aroma and warming taste that can mask the sensory weaknesses of Moringa. This study aims to analyze the reduction of moisture content in raw materials (Moringa and ginger) and to determine the best combination formulation of Moringa leaf powder and ginger based on organoleptic properties (color, aroma, and taste)[cite: 1]. This experimental study was conducted at the Laboratory of Universitas Nahdlatul Ulama Sumatera Utara in July 2026[cite: 1]. Moisture content was tested using the oven method (gravimetry), while organoleptic evaluation was conducted on 9 combination formulations (K1J1 to K3J3)[cite: 1]. The results showed that drying effectively reduced the moisture content of fresh Moringa leaves from 73.38% to 8.89% (dried Moringa leaves) and fresh ginger from 79.73% to 4.54% (dried ginger)[cite: 1]. Organoleptic results showed that sample K3J3 obtained the highest color score (35)[cite: 1], while sample K1J3 obtained the highest aroma score (34) and taste score (29)[cite: 1]. Overall, formulation K1J3 was selected as the best combination formulation with the highest total score (89) in terms of aroma and taste, followed by sample K3J3 (total score 85).